ASSESMENT OF EFFICACY OF THE TISSUE FIXATION SATURATED SODIUM CHLORIDE SOLUTION - Mohammed, Hawaa O H. E; Saad, Amir M. (Journal of Veterinary Medicine and Animal Production, 2021)
The present study was conducted to examine and assess the efficiency of saturated sodium chloride solution as a tissue fixative. Specimens for histological and histopathological investigations where obtained from slaughtered sheep at karrari slaughterhouse in Omdurman. These specimens were taken from skin, brain, lung, liver, kidney, spleen, lymph nodes, pancreas, intestines, cardiac muscles and skeletal muscles. They were fixed in saturated sodium chloride solution as test fixative as well as in 10 % formalin (control) for 2, 15 and 30 days. They were processed and sectioned. The slides were stained with hematoxylin and eosin. The slides evaluated using the light microscope. The results showed that sections of skin, lung, brain, lymph nodes, skeletal muscles and cardiac muscles were well fixed in saturated sodium chloride solution compared with the control sections fixed in formalin for the three fixation periods (2, 15 and 30 days).sections of liver and kidney fixed for 2 and 15days showed good fixation .The spleen and intestine sections showed good results (fixation) in samples fixed in saturated sodium chloride solution for 2 days. However, the pancreas showed autolysis in the parenchyma tissue and lost its histological details in section fixed for 2, 15 and 30 days. On the other hand, the sections of pathological lesions examined, showed clearly the histopathological details.